2009
DOI: 10.1080/00016340902893678
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of intrauterine contraceptive device as a risk factor for tubo‐ovarian abscess

Abstract: The current Medical Products Agency recommendation that a woman nearing the end of her reproductive phase can safely use the same IUCD for a period exceeding five years is challenged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…Bizim vakamızda olduğu gibi tubaovaryan abse, abdominal şiddetli ağrı, ateş, akut batın, vajinal kanama, barsak obstrüksiyonu bulguları ile prezente olan olgu sunumları nadir olarak bildirilmektedir. Retrospektif bir çalışmada 5 yıldan daha uzun süre RİA kullanımının TOA gelişimi için bir risk faktörü olabileceği ancak yinede 10 yıla kadar güvenle kullanılması gerektiği saptanmıştır (8).…”
Section: Discussionunclassified
“…Bizim vakamızda olduğu gibi tubaovaryan abse, abdominal şiddetli ağrı, ateş, akut batın, vajinal kanama, barsak obstrüksiyonu bulguları ile prezente olan olgu sunumları nadir olarak bildirilmektedir. Retrospektif bir çalışmada 5 yıldan daha uzun süre RİA kullanımının TOA gelişimi için bir risk faktörü olabileceği ancak yinede 10 yıla kadar güvenle kullanılması gerektiği saptanmıştır (8).…”
Section: Discussionunclassified
“…The predisposing factors in the development of a TOA include nulliparity, sexual activity, previous episodes of PID, multiple sexual partners, lower socioeconomic status and the use of intrauterine devices [6,9]. Particularly, IUDs are associated with an increased risk for ascending infections [9] with high absolute numbers, especially as they are considered worldwide as one of the most preferred methods of reversible contraception [10].…”
Section: Discussionmentioning
confidence: 99%
“…Her blood parameters on presentation were as follows: haemoglobin tubo-ovarian abscess. (9) The authors also reported that E. coli was the most common pathogenic organism causing tubo-ovarian abscess; they postulated that the increased risk of tubo-ovarian abscess was probably due to a high incidence of bacterial vaginosis. (9) In addition to an increased incidence of bacterial vaginosis, IUDs are also associated with congestion of the bladder trigone.…”
Section: Ca S E R Epo Rtmentioning
confidence: 99%
“…(9) The authors also reported that E. coli was the most common pathogenic organism causing tubo-ovarian abscess; they postulated that the increased risk of tubo-ovarian abscess was probably due to a high incidence of bacterial vaginosis. (9) In addition to an increased incidence of bacterial vaginosis, IUDs are also associated with congestion of the bladder trigone. (10)(11)(12) This congestion can contribute to the development of UTI, accounting for the increased risk of UTI among IUD users.…”
Section: Ca S E R Epo Rtmentioning
confidence: 99%